FORMATION OF MOTIVATIVE ORIENTATION YOUNG TEACHER TO THE IMPLEMENTATION OF INNOVATION (Pedagogy of Higher and Secondary Education, 2007)
The article deals with the problem of formation the motivation trend to the innovation activity of a yang teacher in the system of the school methodical work.